Corrosion inhibition of cold-rolled low carbon steel with pulse fiber laser ablation in water - Chan, Sze Ney; Wong, Wai Yin; Walvekar, Rashmi; , Abdul Amir H. K.; Khalid, Mohammad *; Lim, Kean Long (ASM International, 2018)
This study aims at the use of a fiber laser for modifying the surface properties of cold-rolled low carbon steel via a pulse laser ablation technique in water. The effect on the corrosion behavior of the fiber laser-treated metal surface was investigated in NaCl and HCl environments. Electrochemical tests showed significant improvement in the corrosion resistance of the laser-treated sample in NaCl, with an increase in open-circuit potential (OCP) from − 0.65 to − 0.60 V and an inhibition efficiency of 89.22% as obtained from the impedance study. Such improvement was less significant in an acidic environment. Lower corrosion rates of 20.9 mpy and 5.819 × 103 mpy were obtained for the laser-treated samples in neutral and acidic electrolytes, respectively, than the corrosion rates obtained for the as-received samples (33.2 mpy and 11.98 × 103 mpy). Morphological analysis indicated a passive film built by spherical grains of regular size on the metal surface after laser treatment. The corrosion inhibition effects in NaCl were evident by the nonexistence of the common corrosion products of lepidocrocite and crystalline structures that were seen on as-received samples; only polyhedral crystals with micrograins grown on them were seen covering the laser-treated surface. Therefore, the laser treatment using a fiber laser source improved the corrosion resistance of cold-rolled low carbon steel.